2015
DOI: 10.1517/14712598.2015.1084281
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl hydroxylase inhibitors act as agents to enhance the efficiency of cell therapy

Abstract: The data reviewed here suggest that PHD inhibitors are effective operators in improving stem cell therapy. However, because of some limitations, these compounds should be properly examined before clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 155 publications
0
20
0
Order By: Relevance
“…The most known molecular mechanism that directs migration and homing of mesenchymal stem cells (MSCs) into target tissue is the activation of some chemokine receptors such as CXCR4 . Recent evidence has revealed that chemical agents such as Deferoxamine (DFO) which mimic hypoxic pre‐conditioning can increase cell therapeutic efficacy through increment of stem cells homing factors . DFO is an iron‐chelator drug and a family of prolyl‐4 hydroxylase inhibitor that stabilizes hypoxia inducible factor 1‐ α (HIF‐1α) through the inhibition of prolyl hydroxylases enzyme which target HIF‐1 protein through degradation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most known molecular mechanism that directs migration and homing of mesenchymal stem cells (MSCs) into target tissue is the activation of some chemokine receptors such as CXCR4 . Recent evidence has revealed that chemical agents such as Deferoxamine (DFO) which mimic hypoxic pre‐conditioning can increase cell therapeutic efficacy through increment of stem cells homing factors . DFO is an iron‐chelator drug and a family of prolyl‐4 hydroxylase inhibitor that stabilizes hypoxia inducible factor 1‐ α (HIF‐1α) through the inhibition of prolyl hydroxylases enzyme which target HIF‐1 protein through degradation .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Recent evidence has revealed that chemical agents such as Deferoxamine (DFO) which mimic hypoxic pre-conditioning can increase cell therapeutic efficacy through increment of stem cells homing factors. 9 DFO is an iron-chelator drug and a family of prolyl-4 hydroxylase inhibitor that stabilizes hypoxia inducible Flow cytometry assay showed that BMSCs were positive for CD markers such as CD73 (74.3%) (F), CD105 (92.12%) (G), and CD90 (91.63%) (H), and negative for CD45 (4.6%) (I) and CD34 (2.9%) (J). Isotype control-FITC (D), Isotype control-PE (E).…”
Section: Introductionmentioning
confidence: 99%
“…In hypoxia, the prolyl hydroxylation is blocked and the stabilized alpha subunit translocated to the nucleus, where it dimerizes with the β subunit, and this complex binds to hypoxia‐responsive elements (HRE) within the promoter of hypoxia‐inducible genes . Angiopoietin, VEGF, CXCR4 and matrix metalloproteinase (MMPs) are examples of HIF‐1 target genes, which have important roles in stem cell viability, proliferation and migration …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Angiopoietin, VEGF, CXCR4 and matrix metalloproteinase (MMPs) are examples of HIF-1 target genes, which have important roles in stem cell viability, proliferation and migration. 10,11 Several studies have shown that some of gene products can mimic the cytoprotective effects of hypoxia. These products include stromalderived factor-1 (SDF-1), heat shock proteins (HSPs), erythropoietin (EPO) and inflammatory intermediates, in particular PGE2, which stimulates the overexpression of HIF-1 and other signalling pathway such as extracellular signal-regulated kinase (ERK).…”
mentioning
confidence: 99%
“…HIF‐1 is a heterodimeric transcription factor consisting of O 2 ‐regulated α subunit and a constitutively expressed β subunit that binds to hypoxia‐response element (HRE) within the promoter of hypoxia‐inducible genes. Some of HIF‐1 target genes, including angiopoietin, VEGF, CXCR4, and MMPs are essential factors for stem cell viability, proliferation and migration …”
Section: Introductionmentioning
confidence: 99%